Estimation of mangrove carbon using drone images - Firman Farid Muhsoni; Indah Wahyuni Abida; Dyah Ayu Sulistyo Rini; Aditya Januar Putera (Depik, 2021)
Mangrove has numerous ecological functions, such as a habitat for various biota, a place of care and rearing, with a microclimate regulator and spawning. This ecosystem can store the highest carbon compared to tropical, subtropical, and boreal forests. This research aimed to model the estimation of mangrove carbon stocks using drone images. The method used consists of several steps as follows: (1) Taking and analyzing drone images, (2) Identification and estimation of biomass with carbon stocks, (3) Modeling of mangrove carbon stock using drone and field data. The results of mangrove carbon estimation using logarithmic regression of drone images were the best, by the equation y = 0.0455ln (x) + 0.244. Therefore, the results showed that the R2 value was 0.7454, with the RMSE accuracy-test being 689.9 kg, at 35.4%.Keywords:DronesMangroveCarbon stock